Dynamic trusted access control method and system based on dual-system architecture - KONG JINZHU; YANG ZHAOJUN; WANG ZHEN; WEI LIFENG; JI YIWEN (2022)
The invention relates to the technical field of computer science, in particular to a dynamic trusted access control method based on a dual-system architecture, which comprises the following steps: dividing a computer system into a computing system and a protection system, the computing system comprising a plurality of subjects, a plurality of objects and a plurality of access strategy libraries; the protection system measures whether the computing system is in a trusted state; the computing system detects that a subject accesses an object through an access strategy library in an environment, firstly detects whether a strategy allowing the subject to access the object exists in the access strategy library or not, if not, terminates the access, and if yes, stops the access. And if so, detecting whether the subject, the environment, the access policy library and the object are in an untrusted state. According to the method, the judgment of the dynamic credible state of four elements of the access strategy is add